Osteolysis of the Greater Trochanter Caused by a Foreign Body Granuloma Associated with the Ethibond® Suture after Total Hip Arthroplasty. (31st January 2017) - Kamo, Keiji; Kijima, Hiroaki; Okuyama, Koichiro; Seki, Nobutoshi; Yamada, Shin; Miyakoshi, Naohisa; Shimada, Yoichi
Abstract : The present case shows a case of progression of osteolysis of the greater trochanter caused by a foreign body granuloma associated with the number 5 Ethibond suture in cementless THA with the direct lateral approach that was completely healed by removal of the Ethibond suture. A 55-year-old Japanese woman with secondary osteoarthritis caused by acetabular dysplasia underwent left cementless THA with the direct lateral approach. After setting of the total hip prosthesis, the gluteus medius muscle and vastus lateralis muscle were reattached to the greater trochanter through two bone tunnels using number 5 Ethibond EXCEL sutures. The left hip pain disappeared after surgery, but the bone tunnels enlarged gradually and developed osteolysis at 10 weeks. The removal of the Ethibond sutures and debridement improved the osteolysis. Histological examination showed the granuloma reaction to a foreign body with giant cell formation. The Ethibond suture has the lowest inflammatory tissue reaction and relatively high tension strength among nonabsorbable suture materials. However, number 5 Ethibond has the potential to cause osteolysis due to a foreign body granuloma, as in the present case.